2017
DOI: 10.18632/oncotarget.14915
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-1246 induces pro-inflammatory responses in mesenchymal stem/stromal cells by regulating PKA and PP2A

Abstract: The tumor microenvironment (TME) has an impact on breast cancer progression by creating a pro-inflammatory milieu within the tumor. However, little is known about the roles of miRNAs in cells of the TME during this process. We identified six putative oncomiRs in a breast cancer dataset, all strongly correlating with poor overall patient survival. Out of the six candidates, miR-1246 was upregulated in aggressive breast cancer subtypes and expressed at highest levels in mesenchymal stem/stroma cells (MSCs). Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 102 publications
3
57
0
Order By: Relevance
“…Meanwhile, this study also demonstrated that miR-1246 induced secretion of key pro-inflammatory cytokines and chemokines (IL-6, CCL2 and CCL5) in MSCs was mediated via NF-κB signaling pathway [25]. At the functional level, miR-1246 had been shown to induce the proliferation, invasion and migration and enhance cell apoptosis of cervical or hepatocellular carcinoma cells [28, 29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, this study also demonstrated that miR-1246 induced secretion of key pro-inflammatory cytokines and chemokines (IL-6, CCL2 and CCL5) in MSCs was mediated via NF-κB signaling pathway [25]. At the functional level, miR-1246 had been shown to induce the proliferation, invasion and migration and enhance cell apoptosis of cervical or hepatocellular carcinoma cells [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies dispalyed that different miRNAs could increase or decrease cell apoptosis in OA, such as miR-149 and miR-30b [23, 24]. miR-1246 is associated with inflammation, which is a positive regulator of the immune response of leukocytes, and is also involved in many cellular processes, such as tumor cell proliferation [25]. However, the mechanism of miR-1246 in OA has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has supported that MSCs play critical roles in tumor development and progression, by increasing stemness of tumor cells, stimulating tumor cell migration, promoting angiogenesis, supporting immune responses, and inducing drug resistance. Additionally, MSCs increase the metastatic potential of tumor cells by advancing their motility and invasiveness and thereby play a role in the nature of a metastatic niche at the secondary site (Bott et al, 2017; Donnarumma et al, 2017; Gonzalez et al, 2017; Luo et al, 2009; McAndrews et al, 2015; Wolfe et al, 2016). Therefore, a comprehensive knowledge on the biology and mechanism of interaction between MSCs and TME of breast and prostate cancer is essential for the development of therapeutics that capitalize on vulnerabilities in these tumor cell-MSC interplay.…”
Section: Tumor Cell Interactions With the Mesenchymementioning
confidence: 99%
“…A recent study shows that MSCs in the TME has an impact on breast cancer progression by creating a pro-inflammatory milieu within the tumor (Bott et al, 2017). This study identified six putative oncomiRs, strongly correlating with poor overall patient survival.…”
Section: Tumor Cell Interactions With the Mesenchymementioning
confidence: 99%
“…miRNAs regulate signaling pathways at the post‐transcriptional level and are frequently deregulated in breast cancer. It has been shown that aberrantly expressed miRNAs promote cancer development, metastasis formation, and potently induce drug resistance in both tumor cells and cells of the tumor microenvironment (Bott et al ., 2017; Breunig et al ., 2017; Dvinge et al ., 2013; Tang et al ., 2012; Zhu et al ., 2011). In a previous study, we have identified a tumor‐suppressive function of the miR‐520/miR373 family by targeting TGFBR2 in breast cancer cells (Keklikoglou et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%